Anthocyanin profile and gene expression in berry skin of two red Vitis vinifera grape cultivars that are sunlight dependent versus sunlight independent. (19th May 2013) - Zheng, Y.; Li, J.H.; Xin, H.P.; Wang, N.; Guan, L.; Wu, B.H.; Li, S.H.
Abstract Background and Aims When sunlight was excluded (opacity coefficient 100%) from fruitset until maturity, the red grape cultivar Jingxiu failed to colour while Jingyan (Jingxiu × white grape Xiangfei) developed red colour. The aim of this study was to gain insight into the genetic background that may be responsible for sunlight‐dependent versus sunlight‐independent anthocyanin biosynthesis in berry skin. Methods and Results The composition and concentration of anthocyanins via high‐performance liquid chromatography, and the transcriptional level of structural and regulatory genes via real‐time polymerase chain reaction were investigated. Light exclusion suppressed all the anthocyanins in Jingxiu berry skin, but did not change the proportion of the various anthocyanins in Jingyan. UDP‐glucose:flavonoid 3‐O‐glucosyltransferase (UFGT) and a v‐myb myeloblastosis viral oncogene homolog transcription factor (VvMYBA1) were expressed at a high level in sunlight‐exposed Jingxiu, sunlight‐exposed and excluded Jingyan, but not in sunlight‐excluded Jingxiu, which correlated with phenotypic colouration (red vs not red). There was no difference in the DNA sequence of the VvMYBA1b promoter region between Jingxiu and Jingyan. Conclusions The regulatory gene VvMYBA1 is involved in the regulation of anthocyanin biosynthesis via the structural gene UFGT, while there must be some other regulatory factors or post‐transcriptional regulation mechanisms that differentially regulated VvMYBA1 in Jingxiu and Jingyan in response to sunlight. Significance of the Study The primary control mechanism of anthocyanin biosynthesis in the absence of sunlight would provide information for breeding sunlight‐independent red grape cultivars, which would be valuable for cultivation in areas with low sunlight, e.g. glasshouses or other covered cropping.